Temperature and chemical effects on the interfacial energy between a Ga–In–Sn eutectic liquid alloy and nanoscopic asperities - Han, Yujin; Thebault, Pierre-Marie; Audes, Corentin; Wang, Xuelin; Park, Haiwoong; Jiang, Jian-Zhong; Caron, Arnaud (Beilstein Journal of Nanotechnology, 2022)
The interfacial energies between a eutectic Ga–In–Sn liquid alloy and single nanoscopic asperities of SiOx, Au, and PtSi have been determined in the temperature range between room temperature and 90 °C by atomic force spectroscopy. For all asperities used here, we find that the interfacial tension of the eutectic Ga–In–Sn liquid alloy is smaller than its free surface energy by a factor of two (for SiOx) to eight (for PtSi). Any significant oxide growth upon heating studied was not detected here, and the measured interfacial energies strongly depend on the chemistry of the asperities. We also observe a weak increase of the interfacial energy as a function of the temperature, which can be explained by the reactivity between SiOx and Ga and the occurrence of chemical segregation at the liquid alloy surface.
Keywords: atomic force microscopy (AFM); interfacial energy; liquid alloy